2009
DOI: 10.1158/0008-5472.can-09-1770
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Hypoxia-Inducible Factor 2α Restores p53 Activity via Hdm2 and Reverses Chemoresistance of Renal Carcinoma Cells

Abstract: Abstractp53 mutations are rarely detected in clear cell renal cell carcinoma (CCRCC), but, paradoxically, these tumors remain highly resistant to chemotherapy and death receptor-induced death. Here, we show that the accumulation of hypoxia-inducible factor 2α (HIF2α), a critical oncogenic event in CCRCC following the loss of von Hippel-Lindau (VHL) tumor suppressor protein, leads to Hdm2-mediated suppression of p53. Primary CCRCC specimens exhibiting strong hypoxic signatures show increased levels of activated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 49 publications
5
53
0
Order By: Relevance
“…Several mechanisms of resistance to therapy in relation to p53 have been proposed in the literature: disrupted USP10-mediated deubiquitination of p53 (50), NF-B-dependent suppression of p53 (51,52), and HDM2-mediated suppression of p53 (53,54). Our results suggest an additional mechanism of cell survival in CC-RCC through increased ARC expression.…”
Section: Discussionsupporting
confidence: 55%
“…Several mechanisms of resistance to therapy in relation to p53 have been proposed in the literature: disrupted USP10-mediated deubiquitination of p53 (50), NF-B-dependent suppression of p53 (51,52), and HDM2-mediated suppression of p53 (53,54). Our results suggest an additional mechanism of cell survival in CC-RCC through increased ARC expression.…”
Section: Discussionsupporting
confidence: 55%
“…The resistance of OSRC-2 cells to DOX might be mediated by the factors including the GST, Topo II, overexpression of antiapoptotic gene Bcl-2, and of cell survival gene clusterin and Signal Transducer and Activator of Transcription 1 (STAT1) as well as of hypoxia-inducible factor 2α (HIF-2α). [25][26][27][28][29] It was previously reported that MDA-MB-231 cells do not express P-gp under normal conditions, and where the MDR1 genes (mdr1 mRNA) [30][31][32][33] as well as MRP-1 and BCRP 31) were barely detected; rather the cell expresses P-gp only after a long period of incubation with the drug 31) or when transduced with the MDR1 gene, 34) or under exposure to hypoxic conditions. 35) In MDA-MB-231 cells, the activity of GST, Bcl-2 protein which protects the cell from programmed death and detoxification enzyme cytochrome P450 that rapidly metabolize and inactivate the internalized drugs [36][37][38] would be the possible factors mediating the resistance to DOX.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, FIP200 may promote TSC1 degradation by the ubiquitin-proteosome pathway 134 . HIF2α could also selectively enhance mTORC1 activity by positive effects on growth factor signaling, as HIF2α induces the expression of TGF-α, PDGF-β, and IGF-1, leading to AKT and mTORC1 activation in renal cancer cells 126 . Although additional work is clearly needed to further elucidate the molecular mechanisms by which HIF2α promotes mTORC1 functions, these results reveal another example in which HIF1α and HIF2α antagonize one another to balance hypoxic responses in key growth regulatory pathways.…”
Section: Hifs Oncogenes and Tumor Suppressors - Balancing Hif1α Andmentioning
confidence: 99%